Pemakaian Flat Shoes dan Indeks Massa Tubuh Berhubungan dengan Gejala Plantar Fasciitis pada Mahasiswi Trisakti - Yulizah, Intania; Merijanti, Lie Tanu (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
Introduction: Flat Shoes are shoes that female students often wear. However, the flat model does not provide adequate support for the feet, which increases the risk of plantar fasciitis. Research on plantar fasciitis is more often associated with high heels. In contrast, many women now wear flat shoes daily, most of which are worn by medical students. Purpose: This research aims to assess the relationship between the duration of flat shoe use and Body Mass Index with the occurrence of plantar fasciitis symptoms in female students. Methods: The design of this study is an observational analytic with a cross-sectional approach, using the consecutive non-random sampling method, the sample size consisted of 162 female respondents from the Faculty of Economics and Business at Trisakti University. Data was collected using a questionnaire to determine the duration of shoe use, the Pain Scale for Plantar Fasciitis questionnaire for plantar fasciitis symptoms, also weight and height measurements to obtain the Body Mass Index value. Data analysis using Chi-Square with a significance level of p<0.05. Results: The prevalence of plantar fasciitis symptoms was 18.5%. There was relationship between BMI and the duration of flat shoe use with plantar fasciitis symptoms (p=0.026 and p<0.001). Conclusion: This study concludes a significant relationship between the duration of wearing flat shoes and nutritional status with the symptoms of plantar fasciitis. This research is useful for providing information on risk factors for plantar fasciitis.